2019
DOI: 10.3390/w11081593
|View full text |Cite
|
Sign up to set email alerts
|

A Perception Study of an Integrated Water System Project in a Water Scarce Community in the Philippines

Abstract: The Integrated Water System (IWS) offers alternative water and sanitation services that can potentially benefit rural communities experiencing water scarcity. The IWS described in this study comprises three systems: The Rainwater Harvesting System (RWHS), Water Treatment System (WTS), and Eco-Toilet System (ETS). RWHS and WTS make use of rainwater, which can be utilized for several domestic uses, especially during wet season. ETS has several benefits to users including promotion of environmental and public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Further, some of the other exploratory studies that had contributed to the growing global research outputs on the integrated applications of PLS-SEM and SmartPLS include the articles of Sabri and Afthanorhan (2014), which examined where motivation in a volunteerism program could be derived from and then extended the tool to importance-performance matrix analysis; Ignacio et al (2019) , which predicted the behavioral intention of potential users of a circular economy-based sanitation technology with the combined technology acceptance model and theory of planned behavior (C-TAM-TPB) as the theoretical foundation; Dael et al (2017) , which elucidated the factors affecting the intention to use and intention to learn of the students concerning lectures on bioenergy through a standardized PowerPoint.…”
Section: Partial Least Square - Structural Equation Modeling and Smartplsmentioning
confidence: 99%
“…Further, some of the other exploratory studies that had contributed to the growing global research outputs on the integrated applications of PLS-SEM and SmartPLS include the articles of Sabri and Afthanorhan (2014), which examined where motivation in a volunteerism program could be derived from and then extended the tool to importance-performance matrix analysis; Ignacio et al (2019) , which predicted the behavioral intention of potential users of a circular economy-based sanitation technology with the combined technology acceptance model and theory of planned behavior (C-TAM-TPB) as the theoretical foundation; Dael et al (2017) , which elucidated the factors affecting the intention to use and intention to learn of the students concerning lectures on bioenergy through a standardized PowerPoint.…”
Section: Partial Least Square - Structural Equation Modeling and Smartplsmentioning
confidence: 99%
“…Decentralized wastewater treatment systems are much easier to manage than traditional centralized plants, which are larger and need constant professional supervision. Several studies have confirmed this statement, both among actual system users [51] and potential users alike [52].…”
Section: (C) Perceived Benefitsmentioning
confidence: 73%
“…Transition to CE is quite difficult to initiate, given spare transferable knowledge [50,51] and lack of effective economic instruments able to stimulate farmers to adopt environmentally-friendly solutions. This simple model just reveals how necessity is a better coordination between the business models, governmental policies [52], and the natural systems, given the involvement of different stakeholders [53,54].…”
Section: Discussionmentioning
confidence: 99%